Climate policy costs of spatially unbalanced growth in electricity demand: The case of datacentres - Desta Fitiwi; Muireann Á. Lynch (The Economic and Social Research Institute (ESRI), 2020)
We investigate the power system implications of the anticipated expansion in electricity demand by datacentres. We perform a joint optimisation of Generation and Transmission Expansion Planning considering uncertainty in future datacentre growth under various climate policies. Datacentre expansion imposes significant extra costs on the power system, even under the cheapest policy option. A renewable energy target is more costly than a technology-neutral carbon reduction policy, and the divergence in costs increases non-linearly in electricity demand. Moreover, a carbon reduction policy is more robust to uncertainties in projected demand than a renewable policy. High renewable targets crowd out other low-carbon options such as Carbon Capture and Sequestration. The results suggest that energy policy should be reviewed to focus on technology-neutral carbon reduction policies.
Keywords: 330; Datacentres; generation expansion planning; transmission expansion planning; climate policy; renewable energy